Assessing the Trend and Efficacy of CSR Initiatives on Communities in the FMCG Sector: A Comprehensive Analysis of Companies' Social Impact over Time - Pawaskar, Durva (ATLAS SkillTech University, 2024)
The Colgate Palmolive internship experience has not only expanded understanding of CSR and ESG in the FMCG and Public Listed sectors, but also highlighted the part that businesses play in promoting favourable social and environmental outcomes. The results of the trend analysis and the ESG evaluation offer important new information that can direct Colgate Palmolive's future CSR actions and emphasise how crucial it is to match business aims with sustainable development objectives.
Project Report on Assessing the Trend and Efficacy of CSR Initiatives on Communities in the FMCG Sector: A Comprehensive Analysis of Companies' Social Impact over Time (2022-24) Under the Guidance of Prof. Zuleika Homavazir
Keywords: Colgate; ESG; CSR; FMCG